Hitting Them With Carrots: Voter Intimidation and Vote Buying in Russia. Issue 3 (5th February 2018) - Frye, Timothy; Reuter, Ora John; Szakonyi, David
Abstract : Scholars have identified many ways that politicians use carrots, such as vote buying, to mobilize voters, but have paid far less attention to how they use sticks, such as voter intimidation. This article develops a simple argument which suggests that voter intimidation should be especially likely where vote buying is expensive and employers have greater leverage over employees. Using survey experiments and crowd-sourced electoral violation reports from the 2011–12 election cycle in Russia, the study finds evidence consistent with these claims. Moreover, it finds that where employers have less leverage over employees, active forms of monitoring may supplement intimidation in order to encourage compliance. These results suggest that employers can be reliable vote brokers; that voter intimidation can persist in a middle-income country; and that, under some conditions, intimidation may be employed without the need for active monitoring.